'What Does This Mean?': How UK Companies Make Sense of Human Rights. Issue 2 (25th May 2017) - OBARA, Louise J
Abstract: How do companies understand and talk about human rights? Do they consider human rights a moral, legal or political construct? What type of responsibility do they assume in respect of human rights (e.g., direct/indirect, narrow/broad)? Is the language and label of human rights used within day-to-day practice? This article attempts to address these questions by drawing on empirical data collected as part of an in-depth, qualitative study on the development of human rights within 22 UK companies. Through an analysis based on sensemaking, the article explores the meaning of human rights, the grounds used to justify corporate responsibility, and the human rights terminology and labels employed within the corporate setting. It then analyses what this understanding and discourse means for the debate about the role of private entities for the protection of human rights.